Differential proteomics analysis of the analgesic effect of electroacupuncture intervention in the hippocampus following neuropathic pain in rats - Gao Yong-Hui; Chen Shu-Ping; Wang Jun-Ying; Qiao Li-Na; Meng Fan-Ying; Xu Qiu-Ling; Liu Jun-Ling (BMC, 2012)
Abstract Background Evidence is building steadily on the effectiveness of acupuncture therapy in pain relief and repeated acupuncture-induced pain relief is accompanied by improvement of hippocampal neural synaptic plasticity. To further test the cellular and molecular changes underlying analgesic effect of acupuncture, the global change of acupuncture associated protein profiles in the hippocampus under neuropathic pain condition was profiled. Methods The chronic constrictive injury (CCI) model was established by ligature of the unilateral sciatic nerve in adult Wistar rats. Rats were randomized into normal control (NC) group, CCI group, and CCI with electroacupuncture (EA) stimulation group. EA was applied to bilateral Zusanli (ST36) and Yanglingquan (GB34) in the EA group. Differentially expressed proteins in the hippocampus in the three groups were identified by two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time of flight mass spectrometry. The functional clustering of the identified proteins was analyzed by Mascot software. Results After CCI, the thermal pain threshold of the affected hind footpad was decreased and was reversed gradually by 12 sessions of acupuncture treatment. Following EA, there were 19 hippocampal proteins identified with significant changes in expression (>2-fold), which are involved in metabolic, physiological, and cellular processes. The top three canonical pathways identified were "cysteine metabolism", "valine, leucine, and isoleucine degradation" and "mitogen-activated protein kinase (MAPK) signaling". Conclusions These data suggest that the analgesic effect of EA is mediated by regulation of hippocampal proteins related to amino acid metabolism and activation of the MAPK signaling pathway.